Predictive Value of Highly Sensitive Troponin in Non-ST Elevation Acute Coronary Syndrome - Rauf, Qasim; Ahmad, Munir; Yasir, Muhamnad; Alavi, Muneeb Ahsan; Shaikh, Javed Khurshed; Ghauri, Hamza Azhar; Adil, Muhammad (Journal of Neonatal Surgery, 2025)
Background: Non-ST elevation Acute Coronary Syndrome (NSTE-ACS) is a widespread clinical presentation that needs appropriate diagnosis and risk stratification. High-sensitivity troponin (hs-Troponin) tests have become an important point of reference in identifying myocardial injury faster and more precise than before through conventional tests. To draw a conclusion about the diagnostic and prognostic usefulness of hs-Troponin in the patients with symptoms of NSTE-ACS. Methods: In this prospective observational study, the researchers enrolled 81 patients with chest pain and electrocardiographic results not representing ST-elevation myocardial infarction. They measured the hs-Troponin concentration during admission with the interpretation performed based on a standard threshold. The follow up of the patient was for validation of the NSTE-ACS diagnosis, procedure findings on the coronary angiography, and any adverse event that occurred during hospitalization Results: Elevated hs-Troponin levels were found in 64.2% of the patients. There was a significant association between elevated hs-Troponin and ECG abnormalities, presence of obstructive coronary disease on angiography (p = 0.001), and the need for revascularization (p = 0.001). Patients with elevated hs-Troponin also experienced higher rates of in-hospital major adverse cardiac events. Conclusion: hs-Troponin is a highly sensitive and clinically valuable marker for diagnosing NSTE-ACS and predicting the need for invasive management. Incorporating hs-Troponin into early assessment protocols may improve patient outcomes by enabling prompt and targeted therapy.